2000
DOI: 10.1104/pp.122.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Protein Synthesis and Tolerance of Anoxia in Root Tips of Maize Seedlings Acclimated to a Low-Oxygen Environment, and Identification of Proteins by Mass Spectrometry

Abstract: Tolerance of anoxia in maize root tips is greatly improved when seedlings are pretreated with 2 to 4 h of hypoxia. We describe the patterns of protein synthesis during hypoxic acclimation and anoxia. We quantified the incorporation of [35 S]methionine into total protein and 262 individual proteins under different oxygen tensions. Proteins synthesized most rapidly under normoxic conditions continued to account for most of the proteins synthesized during hypoxic acclimation, while the production of a very few pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
2
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(188 citation statements)
references
References 64 publications
(11 reference statements)
7
174
2
5
Order By: Relevance
“…However, using MS and advanced methods of database interrogation, it is becoming increasingly possible to study the proteomes of organisms with unsequenced genomes. Cross-species identifications have been made in these organisms and others not cited: Zea mays [46,47], Pisum sativum [48,49], Papaver somniferum [50], Spinacia oleracea [44], Arabidopsis thaliana [44], Bos taurus [51], Xenopus laevis [30,52], Pichia pastoris [25], and Trypanosoma brucei [28,29]. Many earlier studies utilizing cross-species identification of unknown proteins relied on high mass accuracy MALDI peptide mapping, and therefore may have identified proteins or enzymes highly conserved across the biosphere.…”
Section: Developments In Genomic Sequencing and The Study Of Proteomementioning
confidence: 99%
See 1 more Smart Citation
“…However, using MS and advanced methods of database interrogation, it is becoming increasingly possible to study the proteomes of organisms with unsequenced genomes. Cross-species identifications have been made in these organisms and others not cited: Zea mays [46,47], Pisum sativum [48,49], Papaver somniferum [50], Spinacia oleracea [44], Arabidopsis thaliana [44], Bos taurus [51], Xenopus laevis [30,52], Pichia pastoris [25], and Trypanosoma brucei [28,29]. Many earlier studies utilizing cross-species identification of unknown proteins relied on high mass accuracy MALDI peptide mapping, and therefore may have identified proteins or enzymes highly conserved across the biosphere.…”
Section: Developments In Genomic Sequencing and The Study Of Proteomementioning
confidence: 99%
“…With the application of MS and sequence similarity methods, a single sequenced genome will enable the identification of more proteins from the proteomes of organisms with unsequenced genomes than by the use of methods that are only able to identify proteins of high homology to database entries. For example, all cross-species identifications in the study of the maize proteome by Chang et al [46] could have been accomplished using database entries from the Arabidopsis genome and sequence similarity searches ( Table 2). Protein sequences from organisms in the left column were used to identify maize proteins by peptide mass mapping.…”
Section: Perspective: Proteomics and Phylogenetic Considerations For mentioning
confidence: 99%
“…[21][22][23] Subsequently, the accumulations of ANPs were shown to be tightly associated with efficient loading of anaerobically responsive transcripts with polysomes. Although a large number of aerobic transcripts are also induced in response to oxygen deprivation, fewer aerobic transcripts are loaded with ribosomes.…”
Section: Post-transcriptional Regulation Of Gene Expression In Submermentioning
confidence: 99%
“…By contrast, a small group of abiotic and biotic stress-induced mRNAs showed a significant increase in polysome association, without a change in abundance. 23,26 Evaluation of mRNA sequences demonstrated that a low GC nucleotide content of the 5'-untranslated region provides a selective advantage for translation under low oxygen. 23,26 These evidences demonstrate that selected synthesis of anaerobic polypeptides involves transcriptional, as well as significant post-transcriptional, regulation of gene expression.…”
Section: Post-transcriptional Regulation Of Gene Expression In Submermentioning
confidence: 99%
“…Combined with mass spectrometry (MS), it allows rapid and reliable protein identification and can provide information about abundance and PTM. In recent years, proteomic-based technologies have been successfully applied to the systematic study of the proteomic responses in many plant species to a wide range of abiotic stresses, including drought (Pinheiro et al, 2005), nutrition deficiency (Alves et al, 2006), temperature (Yan et al, 2006;Sule et al, 2004), oxidative stress (Wang et al, 2004), herbicide (Castro et al, 2005), wound (Shen et al, 2003), anoxia (Chang et al, 2000), salt (Yan et al, 2005) and heavy metal (Labra et al, 2006). Casati et al (2005) have used proteomic technologies to investigate the effects of UV-B on the proteome of the maize leaf.…”
Section: Introductionmentioning
confidence: 99%